Internal Migration in Egypt : Levels, Determinants, Wages, and Likelihood of Employment - Herrera, Santiago; Badr, Karim (World Bank, Washington, DC, 2012)
This paper describes stylized facts about internal migration and the labor force in Egypt, and shows how internal migration in the country is low compared with international standards. Using aggregate labor force survey data, the paper shows how individuals migrate to governorates with higher wages. With a Mincerian equation, the analysis finds that migrants earn premiums with respect to non-migrants, except for those migrants with low education levels. The aggregate labor statistics reveal lower unemployment rates among migrants, a phenomenon that is verified by an employment equation. According to the econometric results, migrants are more likely to be employed, even after controlling for other observable individual characteristics. Finally, the paper estimates a Probit model for the decision to migrate, finding that more educated individuals are more likely to migrate, agricultural workers have a lower probability of migrating, and individuals from governorates in which food production for own consumption is higher are less likely to migrate. These results suggest that low educational attainment and the "food problem", which ties resources to food production to meet subsistence requirements, are at the root of low migration in Egypt.